APPLIED LINGUISTICS THROUGH LITERARY WORLD IN THE POEM OF ??THE GARDEN OF LOVE? BY WILLIAM BLAKE - Aliva Rosdiana (Universitas Islam Nahdlatul Ulama Jepara, 2016)
Applied Linguistics is the academic discipline concerned with the relation of knowledge about language to decision making in the real world. It is used to reveal human language feature expression into language function. Poetry is one of literary world that emphasizes on individual performance and underlies the theory of elocution. Figurative language is a tool that an author employs (or uses) to help the reader visualize (or see) what is happening in a story or poem. There are three types of figurative language used in the application of poem. They are: Metaphore, allusion, and Imagery. ??The Garden of Love? is one best poem ever talking about a church. It is a kind of imagery that refers to a place of a private life of joys and happiness that is the church in a whole light. It is not easy to interpret poetry unless the readers have schematas in their mind.